Sosialisasi Pencegahan Kebakaran di Lahan Gambut Daerah Bereng Bengkel Kota Palangka Raya - Novrianti Novrianti; Nirwana Puspasari; Noviyanthy Handayani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Peat is a type of soil that is formed from the accumulation of half-decaying plant debris, therefore, the content of organic matter is high. (Wikipedia, 2016). The fires of peatlands in Central Kalimantan in 2015 were very severe when compared to previous years. Almost all forests or land experience fires. Land fires do not only occur in forest areas but also within the city of Palangka Raya itself. This is not only triggered by the deliberate burning of land, but also due to natural factors (trees that dry out), strong winds, and also human negligence itself (such as removing cigarette butts in dry forest areas). As a result of extensive forest fires, resulting in smog and causing air pollution which inhibits air and land flight paths, making the prices of basic commodities in Palangka Raya move up. For this reason, it is necessary to hold awareness campaigns on fire prevention on peatlands to the community. In this socialization, information is given to the community about the causes of land fires, how to prevent and overcome them. Based on the results of the socialization, the community better understood the causes of land fires, prevention methods and how to overcome them, so that it was expected to prevent or unravel the occurrence of land fires in the coming years.